In-flight comparison of MOZAIC and POLINAT water vapor measurements - Helten, M.; Smit, H. G. J.; Kley, D.; Ovarlez, J.; Schlager, H.; Baumann, R.; Schumann, U.; Nedelec, P.; Marenco, A. (1999)
An intercomparison of airborne in situ water vapor measurements by two European research projects Measurement of Ozone and Water Vapor by Airbus In-Service Aircraft (MOZAIC) and Pollution From Aircraft Emissions in the North Atlantic Flight Corridor (POLINAT) was performed from aboard the Airbus (MOZAIC) and Falcon (POLINAT) aircraft, respectively. The intercomparison took place southwest of Ireland on September 24, 1997, at 239 hPa flight level. MOZAIC uses individually calibrated capacitive humidity sensors for the humidity measurement. POLINAT employs a cryogenic frost-point hygrometer developed for such measurements. For conversion between humidity and mixing ratio, ambient temperature and pressure measurements on board the respective aircraft are used. The Falcon followed the Airbus at a distance of 7–35 km with a time lag increasing from 30 to 160 s. The water vapor volume mixing ratio measurements in the range of 80–120 ppmv of both instruments are in excellent agreement, differing by less than ±5%, where the trajectories of both aircraft are very close. However, the relative humidity (RH) calculated from POLINAT frost-point measurements and the Falcon PT500 temperature sensor is up to 15% higher relative to the RH of MOZAIC. The agreement improved to within 5% when using the temperature measurement of the PT100 sensor instead of the temperature measurement of the PT500 sensor for RH determination of POLINAT.